2022
DOI: 10.31014/aior.1992.05.04.467
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Demand for Indonesian Tourism

Abstract: Tourism has become one of the largest industries in the world, specifically in Indonesia, where it plays an important role in increasing foreign exchange (FE). Therefore, this study aims to analyze the factors influencing the demand for Indonesian tourism. It used secondary data between 2010 to 2020, with 16 countries selected as samples regarding the ranking of the highest number of tourists. These utilized data contained the following, (1) The number of foreign tourists, (2) National per capita income of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Overall, the issue is how increasing beef production can increase public demand. Along with population growth and community income, it is certain that demand for livestock products will continue to increase, but the progress of livestock productivity is relatively slow due to the increasingly limited area of livestock land and is one of the causes of laceproduction (Rusdi and Suparta, 2016). The decline in beef production in 2019 occurred due to the Covid-19 pandemic where all residents went into lockdown to reduce the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the issue is how increasing beef production can increase public demand. Along with population growth and community income, it is certain that demand for livestock products will continue to increase, but the progress of livestock productivity is relatively slow due to the increasingly limited area of livestock land and is one of the causes of laceproduction (Rusdi and Suparta, 2016). The decline in beef production in 2019 occurred due to the Covid-19 pandemic where all residents went into lockdown to reduce the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The beef sellers come around 03.00 WIB followed by 09.00 WIB the time if non-household consumers and household consumers buy the meat. (Rusdi and Suparta, 2016) Household consumers usually buy beef to be reprocessed for personal and family consumption, for example, meat stews, rendang, meat soup and so on. Beef sellers will experience high demand to coincide with holidays such as Eid al-Fitr, Eid al-Adha, ahead of the fasting month commonly referred to as muploadan, new year and other holidays.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated t value of the independent variable exchange rate is |-2.314| greater than t table |-1.746| and the p-value=0.034, which is less than α=0.05, indicating that there is a significant relationship between the exchange rate and the number of foreign tourist visits if economic growth and inflation are kept constant. The calculated t value of the independent variable inflation is |-1.887| greater than t table |-1.746| and the p-value=0.077 greater than α=0.05, indicating that there is no significant relationship between inflation and the number of foreign tourist visits if economic growth and the exchange rate are kept constant (Wicaksono, 2022;Singagerda, 2013;Medyawati & Yunanto, 2022). On the one hand, foreign tourists may have a particular interest in tourist destinations in a country that is not affected by inflation in that country.…”
Section: Overview Of the Research Objectmentioning
confidence: 96%
“…Furthermore, [34] examined the relationship between exchange rates and tourist visits by using panel data from 2010-2020 and 16 countries of origin of tourists. Based on the fixed effect model, it was found that there is a positive and significant effect of exchange rate, per capita income on tourist demand in Indonesia, and it does not affect prices.…”
Section: Literature Reviewmentioning
confidence: 99%